(Con)trolling the Web: Social Media User Arrests, State-Supported Vigilantism and Citizen Counter-Forces in Russia. Issue 3 (1st October 2020) - Gabdulhakov, Rashid
ABSTRACT: This article applies Haggerty and Ericson's surveillant assemblage concept to the recent wave of social media user arrests in Russia. In doing so, it addresses the legislative frameworks applied to online self-expression, depicts the nuances of legal charges pressed against select social media users, assesses the role of formal law enforcement and vigilant citizens recruited to extend the state's watchful gaze, and elaborates on citizen counter-forces resisting the tightening state control over the digital domain. The article argues that Russia's internet users appear to be trolled by the ruling elite through the use of obscure legal frameworks and the stampede of actors and practices where select individuals face legal charges for their activities on social media, while other users face no consequences for the same engagements. Such unpredictability stimulates self-censorship, making the system effective by virtue of its dysfunctionality. Methodologically, the study relies on desk research and field interviews.